IMPROVEMENT OF MECHANISMS FOR DEVELOPING THE SOCIO-SPIRITUAL ENVIRONMENT IN THE MANAGEMENT ACTIVITIES OF DIRECTORS OF GENERAL SECONDARY EDUCATION SCHOOLS (World Bulletin of Education and Learning, 2026)
This article analyzes the issue of improving the mechanisms for developing the socio-spiritual environment in the management activities of directors of general secondary education schools from a scientific, theoretical and practical perspective. The study developed 22 indicators affecting the school environment, which were divided into high, medium and low impact groups, and an assessment model based on percentage shares (Imm - socio-spiritual environment index) was proposed. Also, the advantages and disadvantages of existing management mechanisms were analyzed and scientifically based proposals were developed for their improvement. The results of the study serve to develop the management competencies of school principals, form a healthy socio-spiritual environment in educational institutions, and scientifically substantiate the decision-making process.
Keywords: Socio-spiritual environment, school management, director competence, indicator system, IMM model, pedagogical environment, educational quality, socio-psychological climate, educational process, management mechanisms.